INFLUENCE GIVING RICE BRAN IMMERSION AT CHICKEN MANURE MEDIA ON THE ABUNDANCE Daphnia magna - Putri, Yulia Eka; Pamukas, Niken Ayu; Hasibuan, Saberina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on 1-15 May 2015 in Environment QualityAquaculture Laboratory. The purpose of this research to know the influence ofrice bran immersion at chicken manure media on the abundance Daphnia magna.The method of research used experimental method with Completely RandomizedDesign (RAL) with five treatments and three replication. The treatments withgiving rice bran immersion at chicken manure media: rice bran control (0 ml/L),D1 (3 ml/L), D2 (5 ml/L), D3 (7 ml/L), D4 (9 ml/L). The result shown rice brangave the highest abundance population of Daphnia magna and best giving is 3ml/L rice bran immersion with top average abundance 569 ind/L.Key word: Daphnia magna, rice bran immersion, chicken manure, abundance